Pengaruh Terapi Komplementer Bekam Basah terhadap Perubahan Darah Rutin Perokok Aktif di Kota Kendari: Penelitian Kuasi Eksperimen - Hadi, Indriono; Rosyanti , Lilin; Askrening, Askrening; Herman, Herman (Health Information : Jurnal Penelitian, 2022)
Smoking can cause chronic hypoxia, increased production of red blood cells, and accompanied by a decrease in plasma volume. Wet cupping therapy is a complementary therapeutic approach that helps to cure disease, balance tissue blood flow, eliminate inflammatory agents and toxins, improve lymph node function and enhance the immune system through the mechanism of blood loss. This study aims to determine the effect of wet cupping therapy on routine blood hematology changes in active smokers. The research was designed using a pre-experimental method with a pre-test and post-test group model. The research was carried out in the PKM Poltekkes building, Ministry of Health Kendari on 26 male respondents aged 20-50 years. The results of the paired t-test statistic showed a significant change in routine blood hematology values ??after wet cupping, this change occurred in the components of WBC, HB, HCT, MCV, MCH, MCHC, with P value < 0.05. Complementary wet cupping therapy is beneficial in restoring the body's balance by strengthening the immune system, eliminating pathogenic factors, and increasing blood circulation. The increase in HB, HCT, MCV, MCH, MCHC in smokers is the main red blood cell index that helps measure the average size and composition of red blood cell hemoglobin in active smokers.